Sustainability in the production process of the cosmetic industry: a literature review (Research, Society and Development, 2022)
The cosmetic industry is a growing economic sector nationally and worldwide. In recent years, the sustainability topic in the sector has caught the interest from consumers, cosmetic industries and organizations. In this sense, this systematic literature review explore the relation between sustainability and the cosmetic industry as the possibility of replacing conventional raw materials with natural and green ones. Data collection was carried out from November 2021 to May 2022, in electronic databases: Scielo, Science Direct, Web of Science, CAPES Periodicals and Google Scholar. For the industrial manufacturing to be considered sustainable, there is a complex facet associated with all phases of the cosmetic product life cycle in environmental, social and economic aspects. However, the most challenging step is the raw material selection phase, since factors such as the safety and function of each ingredient, the formulation stability, the product shelf life time and the consumer preference must be taken into account. There are also many definitions and certifications that end up making the topic confusing and diffuse. Therefore, achieving a more sustainable production in the cosmetic industry is an ongoing process that aims at changes and innovations to develop safe and sustainable alternatives. From the data collected in this review, it is expected that the possibilities of replacing unsustainable synthetic ingredients for sustainable alternative ones will inspire the collaborative efforts by scientific communities and industries to achieve a more sustainable production.